The Relationship Of Arcus Longitudinal Angle With The Type Of Plantar Pedic Curvature in Male and Female Students of The Faculty of Medicine, Wijaya Kusuma University, Surabaya - Muhammad Sergio Ivandry Talib; Ayly Soekanto; Andra Agnez Al Aska (Universitas Muhammadiyah Sumatera Utara, 2022)
Feet have a role as a support for the body when standing or walking, which is very important for carrying out daily activities. Leg length and foot arch have different characteristics depending on gender, environmental conditions, and genetics. One of the health problems that often occurs is musculoskeletal disorders. The most common musculoskeletal disorders are flat feet or commonly known as flat feet. The purpose of this study was to determine the relationship between the medial longitudinal curvature and the type of plantar pedis curvature in male and female students. Faculty of Medicine, Wijaya Kusuma University, Surabaya. This research is a cross sectional research with observational analysis method that uses research data that has been collected and will be continued with the data processing process. The number of samples that meet the criteria is 40 people, then the data is processed by SPSS. Based on the results of this study, the p-value of 0.000 is smaller than (0.05). Based on the results of the study, it can be concluded that there is a significant relationship between the medial longitudinal arch angle and the type of male and female plantar pedis curvature in students of the Faculty of Medicine, Wijaya Kusuma University, Surabaya.Keywords: Arcus Longitudinale Angle, type, Plantar Pedis